Exploration of study objects on the potential of wild mushrooms growing on oil palm empty bunches for learning in the subject of IPAS project at vocational school - Lestari, Lestari; Kusumaningtyas, Pintaka; Erika, Farah (Educational Studies: Conference Series, 2023)
The IPAS Project has a study object in the form of concrete objects and social phenomena found in nature, and it is developed based on empirical experience. This study aimed to find out various alternative study objects regarding the potential of wild mushrooms growing on oil palm empty fruit bunches (OPEFBs) piled at oil palm plantations. The research was descriptive exploratory research. Data were collected through field study, documentation, and literature study. The collected data were analyzed by using thematic analysis from Philip Marrying. The result of the field study found 12 types of wild mushrooms growing on the decayed OPEFBs. Those mushrooms were then identified based on their morphological characteristics. In this study, we found three alternative study objects towards mushrooms growing on OPEFB, which can be developed in the IPAS Project learning: (1) mushroom cultivation using OPEFB waste which includes 4 aspects (living things and their environment, substance, and their changes, earth and space, economic behavior and welfare), (2) morphological characterization for classification of mushroom including 3 aspects (living things and their environment, substance and their changes, social interaction and social dynamics), and (3) detection of chemical compounds present in mushroom, covering 3 aspects (living things and their environment, substance and their changes, economic behavior and welfare).